Design and experimental study of seed precise delivery mechanism for high-speed maize planter - Liu, Quanwei; Cui, Tao; Zhang, Dongxing; Yang, Li; Wang, Yunxia; He, Xiantao; Wang, Mantao (International Journal of Agricultural and Biological Engineering, 2018)
Aiming at improving the seed spacing uniformity of maize planter at high forward speed, a seed precise delivery mechanism driven by electric motor has been developed and evaluated in laboratory. The mechanism was designed to deliver single seed from seed meter to furrow. Seed’s movement from the seed release point in a seed meter to the seed delivery cavity in the belt was analyzed, the mathematical model of seed movement in the seed precise delivery mechanism was established based on seed delivery time analysis. A mechanical prototype was designed and associated control system was developed. The performance contrast experiment was conducted between a traditional seed tube and newly developed seed precise delivery mechanism, and test results indicated that the qualities of feed index of the seed precise delivery mechanism were higher than those of the traditional seed tube delivery mechanism, and the coefficients of variation of the seed precise delivery mechanism were lower than those of the traditional seed tube delivery mechanism when the forward speed of planter was set at 10 km/h, 12 km/h and 14 km/h, respectively. It indicated the seed precise delivery mechanism significantly improved seed spacing uniformity of maize planter compared with the traditional seed tube delivery mechanism. Keywords: seed precise delivery mechanism, electric motor, seed spacing uniformity, delivery time, mechanical prototype DOI: 10.25165/j.ijabe.20181104.2802 Citation: Liu Q W, Cui T, Zhang D X, Yang L, Wang Y X, He X T, et al. Design and experimental study of seed precise delivery mechanism for high-speed maize planter. Int J Agric & Biol Eng, 2018; 11(4): 81-87.